Терракота из раскопок поселения херсонесской хоры Маслины - Латышева, В.А. (My University, 1994)
Latysheva V. A. Terracotta from Excavations of the Settlement of "Maslini" (Dated to IV–II centuries BC) in Chersonessus Khora The article is devoted to publication and analysis of terracotta which was found on "Maslini" settlement of Khersonesus khora. It contains description and characteristic of material, the definition of terracotta’s types, centres of its production, dale, analogy, contents. The analysis of the material shows the predominance of the agricultural cults on khora and also the vitality of the ancient cultural traditions.